Evidence-based management of the acute coronary syndrome (Hanley & Belfus, 2001)
(Hanley & Belfus) Loyola Univ. of Chicago, IL Organizes data gleaned from randomized clinical trials to afford the reader a better understanding of the evidence-based best use of individual forms of evaluation and therapy, and how individual forms of treatment can best be combined to result in optimal patient outcomes. DNLM: Myocardial Infarction--drug therapy.